Art in protest discourses – on the example of the Belarusian anti-government protest movement - Kiklewicz, Aleksander; Mazurkiewicz-Sułkowska, Julia; Pociechina, Helena (Przegląd Wschodnioeuropejski, 2023)
In protest discourses the problem of using aesthetic and artistic elements lies in the centre of attention. The authors draw empirical material from the Belarusian protest movement, especially the anti-government protests of 2020. In the current study the problem of the use of aesthetic elements in protest discourses is considered in two aspects: 1) in the aspect of artistic activism, i.e. the involvement of artists in resistance activities; 2) in terms of the use of aesthetic speech acts in various forms of protest activity, i.e. as a special rhetorical tool with emphatic and persuasive function, but also as a means of expression with the satisfying function. As a result of this dichotomy, the article is divided into two parts. The authors point out that even though public art is not developed in Belarus (e.g. in the field of visual arts), aesthetic creativity is a very characteristic feature of both street poster discourses and forms of protest in the Internet.